Implementasi Program KKN Mengajar Sebagai Upaya Peningkatan Minat Belajar Siswa di SDN 01 Mojowarno, Jombang - Rafi Dwi Nugraha; Anastasya Putri Maharani; Senarita Septia Rosmalia; Stefanus Kristiyanto; Muhammad Rafi; Dhian Satria Yudha kartika (Publikasi Inspirasi Indonesia, 2024)
The low achievement of SDGs in terms of quality education in rural areas remains a challenge, including in Mojowarno village. This activity aims to address this issue by enhancing academic learning quality, environmental awareness, and character education. The teaching and learning process was carried out at SDN 01 Mojowarno, involving 101 students (31 first-grade students, 28 second-grade students, and 42 third-grade students). Through the use of question-and-answer teaching methods and educational media that are auditory, visual, and audiovisual, the results show that this activity benefits the students by fostering curiosity, improving memory and concentration skills, increasing their awareness of environmental issues, and strengthening their moral character. Keywords: Character Education, Environmental Awareness, Participation, Teaching Activities